2021
DOI: 10.3390/cancers13092080
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Regular Aerobic Exercise in Gastric Cancer

Abstract: The benefits of exercise for health-related quality of life (HRQOL) and depression in patients with gastrointestinal disease remain unclear, and studies on gastric cancer are scant. This study examines the association between the maintenance of regular aerobic exercise at a recommended level and depression and HRQOL in patients with gastric cancer during or after treatment. In this cross-sectional study, a face-to-face survey was used to collect data from 126 patients with primary gastric cancer during or afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Furthermore, early exercise can promote gastrointestinal peristalsis and friction between intestinal loops, and reduce the resistance between the gastrointestinal tract and peritoneum, mesentery, and other tissues, so as to maintain stable visceral activities, reduce gastrointestinal discomfort, and facilitate postoperative rehabilitation of patients as soon as possible after surgery. Meanwhile, malnutrition is a common complication of cancer patients, with an incidence of up to 67%, especially in gastrointestinal tumor patients, with a higher incidence of malnutrition [ 11 ]. Nutrition management is an important method for maintaining the tumor patient's nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early exercise can promote gastrointestinal peristalsis and friction between intestinal loops, and reduce the resistance between the gastrointestinal tract and peritoneum, mesentery, and other tissues, so as to maintain stable visceral activities, reduce gastrointestinal discomfort, and facilitate postoperative rehabilitation of patients as soon as possible after surgery. Meanwhile, malnutrition is a common complication of cancer patients, with an incidence of up to 67%, especially in gastrointestinal tumor patients, with a higher incidence of malnutrition [ 11 ]. Nutrition management is an important method for maintaining the tumor patient's nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…Five main advantages related with cancer patients are consistently and actually presented in literature regarding PRO incorporation in daily clinical practice. They are: (1) stepped care models design reflecting patient’s disease pathway [ 4 , 5 , 31 , 32 , 34 , 36 – 57 ] (2) prognosis value [ 2 4 , 22 , 31 , 34 , 37 43 , 47 , 50 , 53 , 57 – 74 ] (3) communication improvements [ 4 , 5 , 10 , 22 , 31 , 32 , 34 , 36 , 38 , 40 43 , 46 50 , 53 , 55 , 65 69 , 71 82 ], (4) patient safety optimization [ 4 , 5 , 10 , 30 , 31 , 34 , 36 , 39 43 , 47 , 48 , 52 , 53 , 55 , 56 , 60 62 , 64 66 , 68 , 70 , 72 74 , 77 87 ] and (5) healthcare risk identification, i.e., unmet problems identification, symptom detection and symptom control [ 2 ,…”
Section: Discussionmentioning
confidence: 99%
“…identified key areas of improvement and confirmed that well-conducted and reported prognostic model studies with a PRO predictor have great potential to improve healthcare delivery [ 38 ]. The physical functioning, global health and QoL domains were consider significant prognostic factors (prognosticators) and several domains have been evidenced [ 39 , 40 , 43 ] including patient-reported functional scores [ 37 , 42 , 60 , 61 , 63 , 68 ], patient-reported symptom interference [ 38 , 49 , 59 , 62 , 65 , 66 ], patient-reported depression [ 96 ], or patient-reported fatigue [ 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle behaviors, such as smoking, [14][15][16][17][18] alcohol intake, [18][19][20][21][22][23] and physical inactivity, 18,[24][25][26][27] have been associated with a high risk of depression. Smoking might lead to depression through effects on the neurotransmitter system, which increases susceptibility to environmental stressors.…”
Section: Introductionmentioning
confidence: 99%